2022
DOI: 10.1002/ange.202200356
|View full text |Cite
|
Sign up to set email alerts
|

The Electronic Origin of Far‐Red‐Light‐Driven Oxygenic Photosynthesis

Abstract: Photosystem‐II uses sunlight to trigger charge separation and catalyze water oxidation. Intrinsic properties of chlorophyll a pigments define a natural “red limit” of photosynthesis at ≈680 nm. Nevertheless, charge separation can be triggered with far‐red photons up to 800 nm, without altering the nature of light‐harvesting pigments. Here we identify the electronic origin of this remarkable phenomenon using quantum chemical and multiscale simulations on a native Photosystem‐II model. We find that the reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…The data further establish that there is no appreciable competition from P D1 —independent of excitation wavelength—indicating that the initial electron acceptor is Phe as supported by the observed vibrational structure at early waiting times. These results are entirely in agreement with the recent theoretical work of Sirohiwal et al where the Chl D1 + Phe CT state was found to be the lowest energy excitation within the PSII-RC with reasonable oscillator strength 41 , 52 . Further, no similarly low energy CT states involving P D1 P D2 were found 41 , thus theoretically excluding the special pair as a candidate for initial CS as our experimental data support.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The data further establish that there is no appreciable competition from P D1 —independent of excitation wavelength—indicating that the initial electron acceptor is Phe as supported by the observed vibrational structure at early waiting times. These results are entirely in agreement with the recent theoretical work of Sirohiwal et al where the Chl D1 + Phe CT state was found to be the lowest energy excitation within the PSII-RC with reasonable oscillator strength 41 , 52 . Further, no similarly low energy CT states involving P D1 P D2 were found 41 , thus theoretically excluding the special pair as a candidate for initial CS as our experimental data support.…”
Section: Resultssupporting
confidence: 93%
“…Such a result is consistent with a recent QM/MM calculation, utilizing range-separated TD-DFT theory and the coupled-cluster theory with single and double excitations (CCSD), which proposed that the lowest CT state was Chl D1 + Phe − 41 . Recent theoretical studies suggest that the lowest CT state among the RC pigments is composed of P + Phe − 51 , 52 and that state, which has very low oscillator strength, can be directly excited by far-red light (in the red tail of, or beyond our laser spectrum) 52 . Our spectra show similar frequencies for Chl D1 + and P + , thus it is possible that there is a small contribution from P + to the signal even at early time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, the RSH kernels CAMY-B3LYP and ωB97-X, which are typically used in computational studies of the PSII RC , give very different results. CAMY-B3LYP is actually in excellent agreement with the experiment and the GW -BSE calculations, while ωB97-X gives much too high excitation energies and also massively overestimates .…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with previous results and our own calculations on the TD-DFT/RSH level for the full hexameric complex also ev GW -BSE and qs GW -BSE only predict states with predominantly local characters in the absence of the protein environment. These states can therefore not be linked to the experimentally observed CT processes. Recent computational studies have established that the environmental electrostatics are responsible for this type of CT. ,, Along the lines of previous GW -BSE implementations, ,, future research needs to focus on ways to explicitly account for the environmental electrostatics in large-scale GW -BSE calculations.…”
Section: Discussionmentioning
confidence: 99%